Simulating the specific absorption rates in different human tissues at 4G frequencies for mobile phones - Adheed Hasan Sallomi; Ghusoon Abduljaleel Ahmed (Bulletin of Electrical Engineering and Informatics, 2023)
Employing electromagnetic waves in mobile communication networks has increased the level of human exposure to electromagnetic fields that may result in concerns about health hazards associated involves the soaking up of cellular phone electromagnetic energy. The human body is penetrated by the electromagnetic fields that emit from a cell phone. The specific absorption rate (SAR) that is generated in the human head and body layers usually expresses the thermal effect on human tissue. The main objective of this paper is to investigate the thermal effects of the electromagnetic field induced inside the human head and body through the construction of a simplified model for both. The RF-source and human body models are built by using the ANSYS high-frequency structural simulator (HFSS). A planar inverted-F antenna (PIFA) will use to assign SAR values to different body tissues for the fourth generation (4G) of mobile phone communication at an operational frequency of 2.6 GHz and power radiated of 125 mW. The model is simulated and analyzed to evaluate the SAR induced at different human tissues depending on the source-to-antenna distance and its generated values must not exceed the safe limits for harmful thermal effects.